Literature and Ecology: Promoting an Eco-Consciousness through Children Literature - Amer, Enas subhi (International Journal of Language and Literary Studies, 2022)
The study scrutinises intermingled relations between children literature and some ecological issues. Such interwoven relationships would be highly recommended to encourage children to explore and identify themselves with nature from early ages to avoid facing an extreme experience later on. The research limits its scope to two novels Suzanne Collins’ (1962) The Hunger Games trilogy (2003-2007) and William Golding’s (1911-1993) Lord of the Flies (1954), and both novels have no direct connections with Ecology and the Eco-consciousness, yet it offers an insightful description about Man’s experience with Nature. Moreover, it raises serious moral questions, raises awareness, heals wounds and suggests solutions for the problems that are both cultural and physical about man’s interactions with nature. The study narrows its theoretical methodology to the thematic contents of literature rather than their form. Nevertheless, theories of ecocriticism such as Serpil Oppermann’s, Cheryll Glotfelty and Harold Fromm are to be mentioned due to their relevance to the main ideas mentioned in the research. The conclusion sums up that the environment is turned to be man’s collective problem rather than a mere didactic issue. This problem is referred to not only as a problem of nature, but also as social, psychological, and cultural problem that negatively affect all components of the earth. It is about a broad perspective which includes human as well as nonhuman nature.